2020
DOI: 10.1108/qmr-04-2020-0050
|View full text |Cite
|
Sign up to set email alerts
|

The role of social media to generate social proof as engaged society for stockpiling behaviour of customers during Covid-19 pandemic

Abstract: Purpose The use of social media and information exchange increased during Covid-19 pandemic because people are isolated and working from home. The use of social media enhances information exchange in a global society, therefore customers are uncertain and not in a better position to take decisions before the situation goes worst everywhere in the world. The current study helps to understand how social media facilitate social and global engagement and information exchange which ultimately leads to the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 45 publications
3
57
0
4
Order By: Relevance
“…Media plays a bidirectional role in the case of PB. Hypothetically, it can increase fear by disseminating pictures of the empty shelves and rumors of a shortage of supply (4,10,11,15). Previous studies revealed that mass media and social media have a role in disseminating fear and rumors, which in turn increases erratic behavior like PB (10,12,18,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Media plays a bidirectional role in the case of PB. Hypothetically, it can increase fear by disseminating pictures of the empty shelves and rumors of a shortage of supply (4,10,11,15). Previous studies revealed that mass media and social media have a role in disseminating fear and rumors, which in turn increases erratic behavior like PB (10,12,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, as an emerging topic with fundamental challenges to study, there is an extreme dearth of empirical studies to ascertain such associations (25). Fortunately, newer studies are coming out even though further studies are warranted (14,15,19). Fourthly, there are numerous confounding variables such as socio-demography, economic construct, previous experience, and the public health crisis itself.…”
Section: Challenges Of Assessing the Relationship Of Social Media And Panic Buyingmentioning
confidence: 99%
See 1 more Smart Citation
“…Such theories are by no means new, however, the way the internet influences their spread is a quickly evolving consideration. This is all the more relevant during the COVID‐19 pandemic, as individuals are forced out of public spaces due to social distancing measures, and the internet becomes more central to how they acquire information about and respond to the pandemic (Koeze & Popper, 2020 ; Naeem, 2020 ; Samet, 2020 ).…”
Section: Conspiracy Theories and The Internetmentioning
confidence: 99%
“…Public attention to correct and conscious online behaviour, especially during the pandemic burden, is crucial to avoid the negative consequence of social media use (Brailovskaia, Cosci, Mansueto and Margraf, 2021). Naeem (2020) emphasised that there should be communication from credible sources regarding how people can handle the health crisis. A study by Casais and Proenca (2020) found that social marketing regarding HIV/AIDS prevention advertisements on television is provided by governments rather than by nongovernment organisation.…”
Section: Problem Statementmentioning
confidence: 99%